(untitled) (Politeja, 2013)
Can we call cardinal Wyszyński the political realist? The Roman Catholic Church was main enemy of communist government in Polish People Republic. Wise leadership of cardinal Stefan Wyszyński prevented this institution from destruction or lost independence. All of his activity had one main purpose – give protection from the plans of communist dignities. So I try to show that cardinal Wyszyński was probably the most realistic person in the history of the Polish People Republic. His attitude was main reason that polish Catholic Church didn’t lost their independence from communist system.